Bolsonaro laughed at it, and so did I: sarcasm as bonding rhetoric in online conversations about cutbacks in education (Intercom - Brazilian Journal of Communication Sciences, 2022)
In light of deliberative theory and based on the concepts of bonding rhetoric and bridging rhetoric (Dryzek, 2010), this article aims to investigate how sarcasm was employed in online conversations on Facebook and YouTube regarding budgetary cutbacks in education made in 2019 by the Ministry of Education (MEC). Sarcasm was the most used argumentative device and was often associated with insults, contributing to a polarized discussion. Sarcastic comments also had low rates of justification, were predominantly declaratory, and largely had a generic or specific target, generating reaction and conflict while strengthening a bond with those who understood the sarcastic meaning behind the message and agreed with the subject who employed it.
Keywords: Online conversation; Deliberation; Rhetoric; Sarcasm; Social Media